Beyond hydrophilic polymers in amphiphilic polymer-based self-assembled NanoCarriers: Small hydrophilic carboxylate-capped disulfide drug delivery system and its multifunctionality and multispatial targetability. (January 2022) - Choi, Yeon Su; Cho, Hana; Choi, Won-Gu; Lee, Sung Su; Huh, Kang Moo; Shim, Min Suk; Park, In Suh; Cho, Yong-Yeon; Lee, Joo Young; Lee, Hye Suk; Kang, Han Chang
Abstract: Due to increasing safety and intracellular delivery concerns about hydrophilic polymers in amphiphilic polymer-based nanoparticles (NPs), this study investigates small hydrophilic molecule-stabilized NPs for effective intracellular delivery with multiorganelle targetability and dual responsiveness to acidic pH/glutathione (GSH). In the construction of small hydrophilic molecule-stabilized NP (MSPCL-NP), the A-B-A-type amphiphilic polymer (MSPCL-P) is composed of two short hydrophilic carboxylate-capped disulfide derivatives (A) that replace hydrophilic polymers and assist in providing colloidal stability and preventing antibody (e.g., at least anti-PEG antibody)-mediated specific interactions and complement activation in the plasma and a hydrophobic multiple disulfide-containing poly(ε-caprolactone) block (B) that carries hydrophobic drugs. The carboxylates on the surface of MSPCL-NP target the acidic extratumoral/endolysosomal milieu by sensing and buffering acidic pH values, and the hydrophobic carboxylic acids improve adsorptive endocytosis and effective endosomal escape. Multiple disulfide linkages selectively target cytosolic GSH, resulting in rapid drug release from the destroyed MSPCL-NP via the cleavage of disulfide bonds in MSPCL-P. Doxorubicin (DOX)-loaded NP (DOX@MSPCL-NP) exerts strong effects on killing cells in vitro and inhibits tumor growth in HCT116 xenograft tumor-bearing mice. In conclusion, the multifunctionality and multispatial targetability of MSPCL-NP might effectively overcome various sequential drug delivery hurdles, ranging from blood circulation to drug release. Furthermore, the introduction of small hydrophilic molecules represents a potential strategy to make self-assembled NPs without the use of hydrophilic polymers.